bahasa inggris - Irma, Dwi Adisa; Handayani, Anita (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study aims to examine the effect of e-wallet usage, financial literacy, and consumptive lifestyle on the financial management of Generation Z in Gresik Regency, East Java. The rapid development of digital financial technology has encouraged the increasing use of e-wallets among young people, especially Generation Z, which may influence their financial behavior and management practices. This research employed a quantitative approach using a survey method. The data were collected from 180 respondents who are Generation Z and active users of e-wallets. The sampling technique used in this study was purposive sampling. Furthermore, the collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) to test the relationships between the research variables. The results of this study indicate that e-wallet usage, financial literacy, and consumptive lifestyle have a significant effect on the financial management of Generation Z. These findings suggest that the increasing use of digital payment systems, supported by adequate financial knowledge, can influence how individuals manage their personal finances. However, a high level of consumptive lifestyle may also affect financial decision-making. This study implies the importance of promoting wise use of e-wallets, improving financial literacy, and controlling consumptive lifestyles in order to support better and more effective personal financial management among Generation Z